PENGEMBANGAN PERANGKAT PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI ALJABAR SMP TAHUN PELAJARAN 2014/2014 - Yustitia, Via; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objectives of this research were: (1) to describe the development of valid and practical Mathematics learning instruments with the scientific approach-based TGT model;(2) to investigate the learning effectiveness with the use of Mathematics learning instruments with the scientific approach-based TGT model on the learning material of Algebra Operation.This research used the research and development method. The development of learning instrument was done by means of 4Ds claimed by Thiagarajan model, et.al. However, this research used only 3Ds, namely: Define, Design, and Develop. The developed learning instruments included lesson plans, studentâs work sheet, and test of problem-solving ability. The subjects exposed to the experimentation were the students in Grade VIII of State Junior Secondary School 2 of Pemalang, State Junior Secondary School 4 of Taman, and State Junior Secondary School 1 of Pemalang. The results of research are as follows: (1) The developed learning instruments are declared as valid ones by the validators; (2) The instruments are also practical because the students have a good response on the developed instruments, the teachers have a good response on the developed instrument, and the lesson plans have been implemented well in the learning process; (3) Â the learning process in the experimental class is effective because the students have good learning activities, the problem-solving ability mean of the students in the experimental class is better than that of the students in control class, and the studentâs problem-solving ability has fulfilled the classical learning completeness.Keywords: development of learning instruments, TGT, and scientific approach